The story and its writer : an introduction to short fiction / Ann Charters - Charters, Ann
During her many years of teaching introduction to fiction courses, Ann Charters developed an acute sense of which stories work most effectively in the classroom. She also discovered that writers, not editors, have the most interesting and useful things to say about the making and the meaning of fiction. Accordingly, her choice of fiction in the first edition of her The Story and Its Writer was as notable for its student appeal as it was for its quality and range. And to complement these stories, she introduced a lasting innovation: an array of the writers' own commentaries on the craft and traditions of the short story. In subsequent editions her sense of what works was confirmed as the book evolved into the most comprehensive, diverse-- and bestselling -- introduction to fiction anthology. Instructors rely on Ann Charters' ability to assemble an authoritative and teachable anthology, and anticipate each edition's selection of new writers and stories